Research protocol for a randomized controlled trial of the health effects of volunteering for seniors - Pettigrew, Simone; Jongenelis, M.; Newton, R.; Warburton, J.; Jackson, B. (BioMed Central Ltd., 2015)
Background: A growing evidence base demonstrates that interventions that focus on participation in physical and social activities can assist in preventing and treating both physical and mental health problems. In addition, there is some evidence that engaging in volunteering activities can provide beneficial social, physical, psychological, and cognitive outcomes for older people. This study will use a randomized controlled trial approach to investigate the potential for interventions involving volunteer activities to produce positive physical and psychological outcomes for older people, thereby contributing to the limited evidence relating to the potential for volunteering to provide multiple health effects. Methods/Design: This randomized controlled trial will involve 400 retired/non-employed individuals in good health aged 60+ years living in the metropolitan area in Perth, Western Australia. Participants will be recruited from the Perth metropolitan area using a variety of recruitment methods to achieve a diverse sample in terms of age, gender, and socioeconomic status. Consenting and eligible participants will be randomly assigned to an intervention (n=200) or control group (n=200). Those in the intervention group will be asked to engage in a minimum 60 min of volunteer activities per week for a period of 6 months, while those in the control group will be asked to maintain their existing lifestyle or take on new activities as they see fit. Physical and psychological outcomes will be assessed. Primary physical outcomes will include physical activity and sedentary time (measured using pedometers and Actigraph monitors) and physical health (measured using a battery of physical functioning tests, resting heart rate, blood pressure, BMI, and girth). Primary psychological outcomes will include psychological well-being, depression, self-esteem, and quality of life (measured using the Warwick-Edinburgh Mental Well-Being Scale, Center for Epidemiologic Studies Depression Scale, the Rosenberg Self-Esteem Survey, and the Global Quality of Life Scale, respectively). Secondary outcomes of interest will include attitudes to volunteering (measured via open-ended interviews) and personal growth, purpose in life, social support, and self-efficacy (measured using the Personal Growth and Purpose in Life subscales of Ryff's Psychological Well-Being Scale, the Social Provisions Scale, and the Generalized Self-Efficacy Scale, respectively). Participants will be re-assessed on these measures after 6 months. Discussion: The results of this randomized controlled trial will generate new knowledge relating to the physical and psychological health benefits of different levels and types of volunteering for older people. In addition, insight will be provided into the major factors influencing the recruitment and retention of older volunteers. Understanding the full potential for volunteering to affect physical and mental well-being will provide policy makers with the evidence they require to determine appropriate investment in the volunteering sector, especially in relation to encouraging volunteering among older people who constitute an important resource for the community. Trial registration: Australian and New Zealand Clinical Trials Registry ACTRN12615000091505. Date registered: 3 February, 2015.